(untitled) (Journal of Universal Science Research, 2025)
The article discusses integration of folk poetry to the formation of national identity, preserving cultural memory and shared values in Seamus Heaney’s poetry. The incorporation of Irish folk elements serves to emphasize and preserve Irish cultural heritage, playing a significant role in the construction of national identity. Seamus Heaney’s engagement with Irish folk poetry is evident in his works, where he often draws upon traditional Irish legends, myths, and oral traditions. Heaney’s poetry captures the essence of Irish culture, connecting contemporary readers with their ancestral past. In poems such as “Maighdean Mara”, “Anahorish”, “Digging”, “Sweeney Redivivus” the poet references ancient rituals and legends, invoking a deep historical and cultural memory.